PHYSICAL PROPERTIES of TELLURITE GLASSES PREPARED UNDER DIFFERENT THERMAL HISTORIES - Araujo, E. B. [UNESP]; Idalgo, E. [UNESP]; Moraes, A. P. A.; Souza Filho, A. G.; Mendes Filho, J. (World Scientific Publ Co Pte Ltd, 2010)
Tellurite glasses were prepared with identical 20Li(2)O-80TeO(2) nominal compositions but with different thermal histories. Differential scanning calorimetry (DSC), X-ray diffraction (XRD) and Raman spectroscopy techniques were used to understand the effects of the thermal histories on the thermal and structural properties of these glasses. It was observed that investigated properties depend strongly on the thermal histories. DSC results suggested that annealing immediately after quenching at temperatures around the glass transition temperature (T(g)) and for longer times is favorable for producing local ordered regions in the glass withoug necessarily increasing the number of nuclei. XRD results revealed the crystallization of the gamma-TeO(2), alpha-TeO(2) and alpha-Li(2)Te(2)O(5) phases in both studied glasses. Raman spectroscopy revealed the metastable character of the gamma-TeO(2) crystalline phase, while the alpha-TeO(2) and alpha-Li(2)Te(2)O(5) crystalline phases persisted up to the final stages of the in-situ crystallization.
Keywords: Tellurite; Raman spectroscopy; X-ray diffraction